An alternative approach to analyze economic ordering quantity and economic production quantity inventory problems using the completing the square method - Omar, M.; Zubir, M.B.; Moin, N.H. (Elsevier, 2010)
In most papers and textbooks, the economic order quantity (EOQ) models and their variants, and the economic production quantity (EPQ) models and their variants are commonly solved using differential calculus. This study proposes an alternative approach that transform the problem into a suitable form and a procedure using the completing the squares method is employed to obtain the optimal solution. The applicability of the method is demonstrated for some selected single and multi-variable problems given in the literature. (c) 2010 Elsevier Ltd. All rights reserved.